Mitigating Occupational Hazards in Renewable Energy Manufacturing: A HIRARC Assessment of Enamelling Operations - Liwun, Stephanus Benedictus Bera; Reyhan Hidayat (Jurnal Ilmiah Teknik, 2025)
This study evaluates Occupational Safety and Health (OHS) risks in the enamelling process of a 150-litre solar water heater tank within a renewable energy manufacturing company, using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method. Conducted through qualitative observations, interviews, and document analysis, the research identified 15 potential hazards—13 high-risk, 1 extreme, and 1 low. Major risks stem from improper use of personal protective equipment (PPE), chemical exposure, and mechanical hazards. Recommended controls include proper PPE usage, engineering improvements, safety training, and better procedures. The findings confirm that HIRARC is effective for systematically identifying and managing workplace risks, fostering a proactive safety culture. The study emphasizes the need for continuous OHS improvement and integration of risk management into daily operations, supporting safer, more sustainable growth in the renewable energy sector.